HUBUNGAN INTERPERSONAL ANTARA DOSEN KEWIRAUSAHAAN DENGAN MAHASISWA PARIWISATA - Fitri Puji Lestari (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2021)
This study aims to determine: (1) Interpersonal relationships between entrepreneurship lecturers and students in terms of the eight factors of lecturer behavior, namely: (a) leadership behavior, (b) helping/friendly behavior, (c) understanding behavior, (d) behavior responsibility/freedom, (e) certain behavior, (f) satisfied behavior, (g) admonishing behavior, (h) strict behavior; (2) Interpersonal relationship structural model testing between entrepreneurship lecturers and students in terms of the eight factors of lecturer behavior.This research is a quantitative research with an expost-facto approach. The population is 1818 students. A sample of 182 withproportional random sampling. Collecting data using a questionnaire with a Likert scale. Data analysis used quantitative descriptive analysis techniques. The results of this study are as follows: (1) Interpersonal Relationsbetween entrepreneurship lecturers and students in terms of eight factors of lecturer behavior showed a positive and significant relationship, (2) a model thattested reflects a fit model.Keywords: Interpersonal Relations, Lecturers, Tourism, Students.